2002
DOI: 10.1001/archotol.128.10.1180
|View full text |Cite
|
Sign up to set email alerts
|

Results of Selective Neck Dissection in Management of the Node-Positive Neck

Abstract: These results support the use of selective neck dissection in carefully selected patients with clinically node-positive squamous cell carcinoma of the head and neck region. Regional control rates comparable to those achieved with comprehensive operations can be achieved in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 20 publications
(26 reference statements)
5
93
0
5
Order By: Relevance
“…Several authors have reported similar control rates with selective node dissection in the N+ neck [9,10]. Andersen et al reported a 94.3 % regional control rates in node positive patients undergoing a SND [11]. Kowalski et al did not find isolated pN+ nodes at level IV or V in their analysis of N+ patients, results similar to this study.…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have reported similar control rates with selective node dissection in the N+ neck [9,10]. Andersen et al reported a 94.3 % regional control rates in node positive patients undergoing a SND [11]. Kowalski et al did not find isolated pN+ nodes at level IV or V in their analysis of N+ patients, results similar to this study.…”
Section: Discussionsupporting
confidence: 87%
“…rates, as long as this does not cause a negative impact on disease control. 15 Several studies have been showing that SND for treating N0 necks and MRND for N+ necks are sufficient for the majority of cases. Careful selection of the type of dissection to be performed, together with judicious indication of postoperative radiotherapy, can improve cure rates as well as the functional and esthetic results.…”
Section: Resultsmentioning
confidence: 99%
“…Careful selection of the type of dissection to be performed, together with judicious indication of postoperative radiotherapy, can improve cure rates as well as the functional and esthetic results. 15 Some studies have recently suggested and others have demonstrated that SND could be used for selected patients with a node-positive neck when they present clinical staging lower than N2A and when there is no capsule rupture. Some authors have suggested using postoperative radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…SBD'nun N(+) hastalarda kullanılabileceğini savunan araştırmacılar da mevcuttur (19)(20)(21). Buna ek olarak süper SBD'nun ileri evre baş-boyun kanseri olan ve kemo-radyoterapi ile tedavi edilen hastalar için etkili bir müdahale olduğu, tespit edilmiştir ( 22 ).…”
Section: Discussionunclassified